Improving the thermal resistance of fluorescent CsPb(Br, I)3 perovskite quantum dots by surface modification with perfluorodecanoic acid. Issue 8 (24th August 2022) - Iso, Yoshiki; Eri, Momoko; Hiroyoshi, Risako; Kano, Kensho; Isobe, Tetsuhiko
Abstract : CsPb(Br, I)3 quantum dots (QDs) show application potential for optoelectronic devices. However, their thermal degradation is a significant problem. In this work, the effects of perfluorodecanoic acid (PFDA) modification on the photoluminescence (PL) and thermal resistance of CsPb(Br, I)3 QDs were evaluated. The PL intensity of oleic-acid-modified quantum dots (OA-QDs) in toluene decreased drastically upon heating at 100°C. The PL quantum yield of the QDs increased from 69.6% to 77.4% upon modification with PFDA. Furthermore, the PL intensity of the QDs modified with PFDA (PFDA-QDs) increased to 140.6% upon heating, because of the reduction of surface defects upon adsorption of PFDA and its optimized adsorption state. A solid-film PFDA-QDs sample heated at 80°C for 4 h showed temporary PL enhancements for the OA-QDs and PFDA-QDs films to 445% and 557% of their initial values, respectively, upon heating for 0.25 h. This was attributed to the optimized adsorption states of the surface ligands. PFDA-QDs film maintained 354% after 4 h of heating, whereas that of OA-QDs film was 104%. Thus, PFDA modification enhances PL intensity and suppresses PL degradation under heating, which is important for wavelength converters for optoelectronic device applications.